Oncogenic activation of the PI3-kinase p110β isoform via the tumor-derived PIK3CβD1067V kinase domain mutation - Pazarentzos, E; Giannikopoulos, P; Hrustanovic, G; St John, J; Olivas, V R; Gubens, M A; Balassanian, R; Weissman, J; Polkinghorn, W; Bivona, T G (Oncogene, 2016)
Activation of the phosphoinositide 3-kinase (PI3K) pathway occurs widely in human cancers. Although somatic mutations in the PI3K pathway genes PIK3CA and PTEN are known to drive PI3K pathway activation and cancer growth, the significance of somatic mutations in other PI3K pathway genes is less clear. Here, we establish the signaling and oncogenic properties of a recurrent somatic mutation in the PI3K p110β isoform that resides within its kinase domain (PIK3Cβ D1067V ). We initially observed PIK3Cβ D1067V by exome sequencing analysis of an EGFR-mutant non-small cell lung cancer (NSCLC) tumor biopsy from a patient with acquired erlotinib resistance. On the basis of this finding, we hypothesized that PIK3Cβ D1067V might function as a novel tumor-promoting genetic alteration, and potentially an oncogene, in certain cancers. Consistent with this hypothesis, analysis of additional tumor exome data sets revealed the presence of PIK3Cβ D1067V at low frequency in other patient tumor samples (including renal cell carcinoma, glioblastoma multiforme, head and neck squamous cell carcinoma, melanoma, thyroid carcinoma and endometrial carcinoma). Functional studies revealed that PIK3Cβ D1067V promoted PI3K pathway signaling, enhanced cell growth in vitro , and was sufficient for tumor formation in vivo . Pharmacologic inhibition of PIK3Cβ with TGX-221 (isoform-selective p110β inhibitor) specifically suppressed growth in patient-derived renal-cell carcinoma cells with endogenous PIK3Cβ D1067V and in NIH-3T3 and human EGFR-mutant lung adenocarcinoma cells engineered to express this mutant PI3K. In the EGFR-mutant lung adenocarcinoma cells, expression of PIK3Cβ D1067V also promoted erlotinib resistance. Our data establish a novel oncogenic form of PI3K, revealing the signaling and oncogenic properties of PIK3Cβ D1067V and its potential therapeutic relevance in cancer. Our findings provide new insight into the genetic mechanisms underlying PI3K pathway activation in human tumors and indicate that PIK3Cβ D1067V is a rational therapeutic target in certain cancers.